Stabilization of peat by deep mixing method: a critical review of the state of practics - Islam, S.; Hashim, Roslan (2008)
The purpose of this paper is to advance the knowledge on peat soil stabilization by critically examining and documenting the current state of practice. Deep Mixing method is emphasised on column type techniques using lime/cement. This paper is essentially a comprehensive review of available academic literature on deep soil stabilization utilizing this approach. Deep mixing with lime or lime-cement column and combined soil stabilization with vertical columns (CSV) methods are discussed and to illustrate applications of these methods in a variety of conditions, several case histories are presented.